CHARACTERISTICS OF NON-SMALL CELL LUNG CARCINOMA AND THE RESULT OF EPIDERMAL GROWTH FACTOR RECEPTOR TEST - Teja Koswara; Jusron Iriawan; Fiona Surya (Journal of Health and Dental Sciences, 2022)
ABSTRACT Lung carcinoma is cancer that develops from the abnormal proliferation of lung epithelial cells. Lung carcinoma has two forms: Non-Small Cell Lung Carcinoma (NSCLC) and Small Cell Lung Carcinoma (SCLC). NSCLC makes up 85% of lung carcinomas cases. EGFR overexpression is often seen in NSCLC. This research aims to discuss and provide information about the patient's characteristics, smoking status, functional status, clinical stage, histopathological diagnosis, and EGFR test of NSCLC. This research is a literature study that collects, manages, uses and reviews research data from scientific journals, previous research manuscripts, and textbooks. The literature review results were that most patients with NSCLC were found in the 55–65 age group. NSCLC can happen to both genders. NSCLC was found in smokers and non-smokers. The patient's functional status was mostly "very dependent". The clinical stage of NSCLC patients is often found in stages III and IV. The most common histopathological diagnosis of NSCLC was adenocarcinoma. EGFR results can be positive or negative; most occur in the adenocarcinoma subtype. EGFR overexpression in NSCLC occurs due to somatic mutations in the tyrosine kinase domain, causing continuous signal transduction and phosphorylation. DOI : 10.54052/jhds.v2n2.p343-354